Hak Kebendaan Pengidap Gangguan Jiwa Dibawah Pengampuan Di Balai Harta Peninggalan - Aryanto, Aisyah Octavianita; Wahyudi, Eko (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
This research explores the implementation of legal protection for the property rights of individuals who experience mental disorders and are under guardianship at the Surabaya Heritage Center. Using a qualitative approach and analysis of primary and secondary data, this research identifies existing protections and evaluates the extent of their effectiveness in ensuring the material rights of vulnerable individuals. The Civil Code regulates that a person suffering from a mental disorder must be accompanied by someone who is being monitored and given the opportunity to appoint a representative who can be trusted to protect them in the future, precisely in Articles 433 to 461. Care at the Inheritance Hall after a decision by the Court is an action that must be carried out by the guardian to maintain Kurandus' rights to take legal action on Kurandus' property. It is hoped that the results of this research will provide better insight into the challenges and opportunities in strengthening legal protection for people with mental disorders who are under guardianship in Surabaya, as well as provide policy recommendations for further improvements in the protection system. People under guardianship also have the right to property, whatever its form, as long as it is obtained legally, so the state has an obligation to protect civil rights as well as the property even if the owner is under guardianship. It is hoped that this research can provide education to the wider community so that in the future it can increase legal awareness which has the impact of forming a legal culture around the protection of property rights for people in custody so that justice and the legal function of social control tools can operate or be enforced to support development of a human generation that is friendly to people with disabilities and implements the principle of equality before the law.